Street Trade Block Leaders and the Governance of Street Trade: Narrating Untold Stories in Inner City Johannesburg - Mmbulaheni, Kwashaba (University of the Witwatersrand, Johannesburg, 2015)
Street trading management is relatively undocumented and quite complex. This entails dealing with informality, mobility, fluidity, survivalism and entrepreneurship, competition over land uses, and complex politics. There is limited understanding of municipal management and its every day practice in Johannesburg. Municipal management is characterised by opacity, rumours of corruption and informal practices. One character in this system through which the everyday practice of street trading management can be approached is the trader block leader. A street trader block leader is an elected representative of traders who negotiates and communicates with the municipal management on behalf of traders. A Block leader is a street trader that has been allocated space formally by municipal management according to the CoJ policy. They have to occupy a designated space like any other trader. From the managements view point a trader block leader is the eyes and ears of management on the street. Block leaders play the part of a broker mediating between state and traders. They can also be viewed as an extension of the state at street level because they receive 20% discount on rentals as a reward for their work. The purpose of this research is to explore, present and analyse street trading management at street level in inner city Johannesburg, through the lens of block trader leaders discourses and practices, at the interface between state and traders.
Planning Honours Report 2015, Wits University
Keywords: street trading management, Johannebsurg, trader block leaders, municipality